(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This research aims to clarify the nature of the relationship of correlation and impact of capital structure in the financial results of commercial banks in Iraq. To obtain this goal, a simple linear regression method was applied to the dependent and independent variables. Secondary data were collected from audited annul financial reports of 10 Iraqi banks listed on the Iraqi Stock Exchange (ISX), which covered a period of eight years from 2015 to 2022 and was statistically analyzed. The dependent variable was the bank’s performance indicator, which was calculated through return on equity (ROE), as well as the bank’s capital structure, which was considered as an independent variable was computed by total liabilities-to-equity ratio (LER), equity-to-assets ratio (EAR), and bank asset growth (BAG). The results reveal a positive correlation between (ROE) and both (LER, BAG) and a negative correlation with (LER) and liability-to-equity ratio (LER) positively and significantly impacts on return on equity, while an insignificant favorable impact on the banks current years performance (ROE) by equity-to-assets ratio (EAR) and bank asset growth (BAG) were noticed. Accordingly, the current research, suggests that Iraqi commercial banks should safe adequate amount of capital to evade form any financial risks and enhance profitability to survive